Hazy Days: Forest Fires and the Politics of Environmental Security in Indonesia - Scott Adam Edwards; Felix Heiduk (Journal of Current Southeast Asian Affairs, 2015)
The Indonesian â€œhazeâ€ that engulfs Southeast Asia is a result of the burning of forests and has a detrimental effect on the health of millions of people. Indonesia is currently the third largest emitter of carbon dioxide in the world. In response to the dangers posed by forest fires to national and global environmental security, the then Indonesian president publicly declared a â€œwar on hazeâ€ in 2006 and called for the use of all necessary measures to stop the deliberate setting of fires. Although his strong â€œsecuritisingâ€ rhetoric received much public support, it is yet to produce results. The Indonesian authorities have had little success in preventing fires or prosecuting the culprits. Indonesia thus appears to be a null case â€“ that is, a case of an unsuccessful securitisation. We argue that this unsuccessful securitisation needs to be understood against the backdrop of Indonesiaâ€™s vast decentralisation process, which resulted in certain powers being devolved from Jakarta to the provinces. We find that it is the ability of local and regional elites (often entrenched in patronage networks with plantation owners) to curtail environmental policies which explains the continuation of forest fires. With regard to securitisation theory, our findings suggest that securitising moves and audience acceptance do not necessarily lead to the successful implementation of emergency measures. It appears that there are intermediate factors â€“ in our case mainly linked to the nature of and the distribution of power within the political regime â€“ that impact on the success of securitisation processes.